(untitled) (Construction Economics and Building, 2012)
Construction sites around the world employ large numbers of people from diverse cultural backgrounds. The effective management of this cultural diversity has important implications for the productivity, safety, health and welfare of construction workers and for the performance and reputation of firms which employ them. The findings of a three year, multi-staged study of cultural diversity management practices on construction sites are critiqued using social identity theory. This reveals that so called “best-practice” diversity management strategies may have an opposite effect to that intended. It is concluded that the management of diversity on construction projects would benefit from being informed by social identity research.